THE INFLUENCE OF DRONE LARVAE HOMOGENATE ON THE QUALITY OF SPERM PRODUCTION IN BREEDING BOARS - Shostya, A. M.; Yemets, Ya. M.; Moroz, O. G.; Stupar, I. I.; Pavlova, I. V.; Maslak, M. M. (Scientific Progress & Innovations, 2019)
The present stage of the reproductive biotechnology development is characterized by wide using the methods of environmentally-friendly influence on the reproductive capacity of animals, among which a special place is given to using natural stimulants of animal origin, one of which is drone larvae homogenate. The purpose of the research was to determine the influence of drone larvae homogenate on the formation of pro-oxidant-antioxidant homeostasis and sperm quality of breeding boars. In the process of research, the following tasks were performed: to study the influence of drone larvae homogenate on qualitative and quantitative indices of sperm production; to find out the peculiarities of pro-oxidant-antioxidant homeostasis formation due to the influence of this biologically active admixture; to determine the impregnation capacity of boars’ sperm after sows’ insemination. Adult boars of the Large White breed, analogues by age, live weight and the quality of sperm production were used in the experiment; the boars were fed with drone larvae homogenate. It was found that additional feeding boars with drone larvae homogenate significantly influences the semen qualitative and quantitative indices: increases the weight of the ejaculate by 10 %, the concentration of spermatozoids is increased by 16.1 %, the number of spermatozoids in the ejaculate – by 33.5 %, the spermatozoids’ motility is increased by 10.6 %, and their survival rate is increased by 14.7 %. These positive effects last for at least a month, which is manifested by a larger ejaculate weight (p <0.001), the number of live spermatozoids in ejaculate (p <0.001), as well as their mobility (p <0.001) and survival (p <0.001). The considerable impact of feeding boars with drone larvae homogenate on the formation of pro-oxidant antioxidant homeostasis in semen was established, which was manifested in slowing down peroxidation processes, confirmed by the lower content of DC and the higher activity of superoxide dismutase by 30 % and catalase – by 12.8 %. The ejaculates of breeding boars receiving the admixture in the final period are characterized by a higher level of antioxidant protection system: the greater activity of superoxide dismutase (p <0.001) and catalase (p <0.01), as well as saturation with ascorbic acid and reduced glutathione. It was established that inseminating sows with semen doses of breeding boars, using drone larvae homogenate, increases impregnation and prolificacy of sows. The effect of this biologically active admixture lasts for at least 30 days.